(3eHGOF EOGQI GdYedjGJ (B:s (3hXGFa h YedjGJ efXeGJ GdGYeGd (B/s - (3GdOhQj, RcQjGs; (3GdYRGhj, fLe hBNQhf s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2010)
(3GdJZjjQ h GdJWhjQ GdJfXjej, Md GdeTcdGJ h GJNGO GdbQGQGJ EOGQI GdJShjb , GdGOGQI GdeGdjI , , GOGQI GdehGQO GdHTQjI ,GOGQI GdYedjGJ h GdNOeGJ , eY hLhO CSFdI aj fgGjI cd aUd(B.s
(3eQGLY U(B.359s
Keywords: (3EJNGP GdbQGQGJ(B- (3GdEOGQIs; (3EOGQI GdCYeGds; (3EOGQI GdCaQGOs